WOUND DISEASE: PREVENTION AND TREATMENT - Aminova Mohinur Normurod's daughter; Ziyodullayev Abdumajid Alijon oʻgʻli; Salaev Atamurod Bahadir oʻgʻli; Aliyorova Marjona Dilshodovna; Khalilov Davron Bakhtiyorovich (Journals Park Publishing, 2022)
This article provides feedback on wound disease and its prevention and treatment.
Keywords: Wound, lymph node, ulcer, condyloma microorganism, antibiotic, penicillin, spirochete